HLA DRB1* ASSOCIATION WITH REPRODUCTIVE DISORDERS IN WOMEN - L. A. Gordeeva; A. V. Shabaldin; A. N. Glushkov; O. A. Glushkova; O. S. Makarchenko; T. A. Simonova; I. V. Vetrova; E. A. Sherina; N. K. Zhilinskaya; V. I. Minina (Медицинская иммунология, 2014)
Abstract. HLA DRB1* gene associations with idiopathic fetal losses and infertility were studied in women. It was shown that idiopathic fetal losses are associated with HLA DRB1*04 specificity, whereas infertility correlated with HLA DRB1*04/07 genotype. The associations revealed may indicate to a special role of autoimmune events in women during pregnancy. The authors suggest a hypothesis on existence of several immune modes of reproductive losses. HLA genotyping may be applied as a basic technique for their determination.